An Andean landscape as a habitat for a specific fauna, Chile - Jaime-Muñoz, Eduardo A. (2024)
The objective of this article was to analyze the natural environment of the pastures of El Rincón, in the province of Limarí, where a community of wild birds lives. The methodology used included field work with direct observation, application of recording sheets for the sighted individuals, creation of cartography with the ArcMap 10.1 program, taking photographs, and making illustrations of birds using Giotto pencils, block, charcoal pencil, eraser. common and moldable rubber. In addition, a bibliographic review was carried out to complement the data obtained. The findings revealed the presence of nineteen species in three different geographical areas. These birds coexist in a habitat threatened by forest fires, deforestation of native forests and climate change. Among the species observed, the turkish is endemic, the tench is quasi-endemic and the partridge is endemic. A thematic map of the study area is also presented along with four illustrations of some of the birds seen.